ANALISIS KORELASI UNTUK MENGETAHUI HUBUNGAN PEMBELAJARAN P5 TEMA KEARIFAN LOKAL TERHADAP AKHLAK SISWA - Wardani, Dian Kusuma; Aisa, Aufia; Alfajar, Ameliya Wahyu (As-Sulthan Journal of Education, 2025)
The Pancasila Student Profile Strengthening Project with a local wisdom theme is a project-based learning approach that aims to foster students' love for their regional culture. The purpose of this research is to investigate the relationship between the Pancasila Student Profile Strengthening Project learning with a local wisdom theme, specifically the habit of speaking Javanese, and the morals of students in a particular class. The respondents of this research were 31 sixth-grade students. The data collection methods used were observation, interviews, questionnaires distributed to respondents, and documentation. Data analysis used correlation analysis to measure the relationship between the P5 learning variable with a local wisdom theme and student morals. The research results show that the relationship between P5 learning with a local wisdom theme and student morals is 0.693, which is positive, with a significance value of 0.000 < 0.05. This means that there is a strong positive relationship between P5 learning with a local wisdom theme and student morals.